Proceeding of the second international conference on sustainable built environment (ICSBE) : livable cities in the fast-growing countries, Yogyakarta 10-12th July 2012 / chairman, Mochammad Teguh...[et.al] - Mochammad Teguh (Faculty of Civil Engineering and Planning Universitas Islam Indonesia, 2012)
x, 582 halaman : ilustrasi, tabel, grafik ; 30 cm